2002
DOI: 10.1590/s0034-72992002000200017
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação auditiva em escolares

Abstract: Introdução: A avaliação auditiva na faixa etária escolar é necessária para a identificação e correção precoce das alterações auditivas. Objetivos: Identificar e quantificar as alterações audiométricas mais freqüentes em escolares. Casuística e Método: Pesquisa realizada com 121 escolares da 1ª a 8ª séries, faixa etária de 7 a 14 anos no mês de novembro de 1998 na cidade de Goiânia, por médicos otorrinolaringologistas e fonoaudiólogos através de exame clínico otorrinolaringológico, audiometria tonal e imitâncio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
11
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 5 publications
5
11
0
5
Order By: Relevance
“…The results showed statistically significant difference in the basic audiological evaluation and high incidence of changes of middle ear and hearing deviant from normality, in the children from the GE, with higher incidence of hearing loss of the conductive type ( Table 1). The findings of the peripheral auditory evaluation are consistent with the literature, noting a high incidence of hearing loss of the conductive type schoolchildren (18,23) . Conductive loss must be identified and treated as early as possible, since hearing degradation can impair school performance, due to the loss of details that a sound information can possess (24) .…”
Section: Discussionsupporting
confidence: 89%
“…The results showed statistically significant difference in the basic audiological evaluation and high incidence of changes of middle ear and hearing deviant from normality, in the children from the GE, with higher incidence of hearing loss of the conductive type ( Table 1). The findings of the peripheral auditory evaluation are consistent with the literature, noting a high incidence of hearing loss of the conductive type schoolchildren (18,23) . Conductive loss must be identified and treated as early as possible, since hearing degradation can impair school performance, due to the loss of details that a sound information can possess (24) .…”
Section: Discussionsupporting
confidence: 89%
“…The tympanometry is a quick and objective test designed to evaluate the functional integrity of the tympanic-ossicular system 7,36 , and that has been broadly used in hearing screening programs for precisely identifying conductive alterations. Like in this study, other authors have also observed the predominance of type A curves 37,38 , followed by type C, when performing the tympanometry in the school-age hearing screening 2,7,22,27 .The occurrence of 26.5% of types B, C, As and Ad tympanometric curves in this study's population, which may be related to middle ear and/or auditory tube alterations, infers that the findings were compatible with Therefore, the regular hearing screening of children during their school years would guarantee that they were affected by hearing loss or other preventable alterations. Information in this study demonstrate the importance of prioritizing the identification and early treatment of hearing impairments.…”
supporting
confidence: 87%
“…It is worth emphasizing that the data collection for the present study was performed in these seasons. This type of hearing impairment is the most reported fail in the school-age hearing screening, both in national and international literature 10,22,32,38 . The combination of procedures to identify children with hearing impairments is recommended because children often fail only one of them 6 .…”
mentioning
confidence: 99%
“…The auditory attention of students can be influenced by hearing impairment, causing impairment in attention and comprehension skills and thus compromising the performance and learning of these children. Thus, it became essential to realization of audiometry and impedance prior to application of SAAAT (19).…”
Section: Discussionmentioning
confidence: 99%
“…For professionals in health and education is essential to understand the effects of these variables in the skills of attention, since the sustained attention and vigilance, when altered, cause difficulty concentrating on the task at the expense of development and learning (2,(18)(19)(20)(21)(22). Given this context, the objectives of this study were to assess the effect of length of day and type of school attended by children in their ability to sustained auditory attention.…”
Section: Introductionmentioning
confidence: 99%